Child-Friendly Schools and Psychosocial Well-Being: A Community-Based Approach to Reducing Verbal Violence in Early Childhood Education - Lailiyah, Nur; Pitoyo, Andri; Lestariningrum, Anik; Wijaya, Intan Prastihastari; Khan, Rosa Imani; Supriyadi, Stevanus Gatot; Vega, Amelia; Kinami, Atina Nafi’a; Octarina, Nadya (CV. Srikandi Kreatif Nusantara in collaboration with Institut Teknologi Mojosari Nganjuk, 2025)
This socialization discussed the importance of developing a Child Friendly School environment as a strategic effort in preventing verbal violence and strengthening children's mental health. Verbal violence that often occurs in school settings leaves a significant long-term psychological impact on children's development. Through a comprehensive approach, Child Friendly Schools offer a framework that supports children's rights, builds positive communication, and creates an emotionally safe learning environment. The program integrates positive communication training for educators, the development of a character education curriculum and the implementation of a sustainable psychosocial support system. By involving all school components, including teachers, staff, students and parents, Child-Friendly Schools not only mitigate verbal violence but also build a strong mental health foundation for future generations. This socialization presents good practices of program implementation in various schools along with an evaluation of its impact in reducing the number of verbal violence and improving children's mental health indicators.